"Take me seriously": A qualitative interview study exploring healthcare experiences of endometriosis patients. - Lara Brauer; Werner de Cruppé; Max Geraedts (PLoS ONE)
Introduction Endometriosis is a chronic disease associated with stigmatisation and delayed diagnoses. In order to create or improve positive healthcare encounters for patients, this study aimed to explore the experiences of women with endometriosis and to identify challenges and resources for these patients. Methods Qualitative, semi-structured interviews were conducted to explore lived experiences of endometriosis patients. A purposive sampling strategy was used, and patients were included if they had a laparoscopically confirmed diagnosis and at least one contact with the healthcare system in Hesse, Germany. Interviews were conducted between May and August 2023, transcribed, and analysed according to an interpretive phenomenological approach using MAXQDA 24. Results In total, 21 women aged 23-54 years (median: 32 years) were interviewed. Three themes were identified, with ambivalence emerging as the common essence of experiences. Patients reported that their experiences were influenced by the role of the healthcare provider, described as either a source of support or an inhibitor in the treatment process. Additionally, patients reported that provider-patient-communication was characterised by both trivialisation and dismissal of symptoms, as well as empathic, encouraging interactions. Limits in the healthcare system, such as the allocation of specialised care, and resources like increased awareness of endometriosis, represented systemic influences on experiences. Conclusion This study provides an insight into the ambivalent nature of healthcare experiences from the perspective of endometriosis patients and contributes to a better understanding of patients' needs in healthcare encounters, which may help to create a more positive healthcare experience for them.